First detection of the cosmopolitan invader Leptoglossus occidentalis Heidemann (Heteroptera: Coreidae) in Argentina - Kun, Marcelo Eduardo (2019)
Leptoglossus occidentalis Heidemann is a conifer seed bug, native to North America. This species is considered invasive and has reached several countries in the Northern Hemisphere and most recently Chile in South America. This work reports the first detection of this species in Argentina, with specimens from the Rio Negro province, in 2017. Ecological traits and its potential rapid spread were also discussed.